Synthesis and Characterization of an Ion-Imprinted Polymer for Selective Adsorption of Copper Ions in Aqueous Solution - Hui Xu; Donghong Guo (Adsorption Science & Technology)
Cu(II) ion-imprinted polymer (IIP) was prepared by a surface molecular imprinting technique using Cu(II) as the template ion, aniline as the functional monomer, attapulgite (ATP) as the support and epichlorohydrin (ECH) as the cross-linking agent. In this study, the IIP was characterized using scanning electron microscope and Fourier transmission infrared spectrometry, and then the factors affecting adsorption were discussed. The selectivity and adsorption capacity for the Cu(II) ions on Cu(II) IIP were systematically studied. Under optimal conditions, the results of this study revealed that the IIP possesses a very strong adsorption and recognizing ability for the Cu(II) ions. The maximum adsorption capacity of IIP for Cu(II) was about 32.0 mg/g and its selectivity is twice that of a non-imprinted polymer. When the Cu(II)-polyaniline/ATP IIP was used repeatedly, its adsorption capacity remained constant.